2019
DOI: 10.1002/ana.25452
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking interhemispheric imbalance as a target for stroke neurorehabilitation

Abstract: Objective: Patients with chronic stroke have been shown to have failure to release interhemispheric inhibition (IHI) from the intact to the damaged hemisphere before movement execution (premovement IHI). This inhibitory imbalance was found to correlate with poor motor performance in the chronic stage after stroke and has since become a target for therapeutic interventions. The logic of this approach, however, implies that abnormal premovement IHI is causal to poor behavioral outcome and should therefore be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 32 publications
3
78
0
3
Order By: Relevance
“…However, Young et al argued that this result could not be generalized to patients with cortical lesions because they found an ipsilesional lateralization during movements of affected hands at baseline toward a bilaterally distributed activity after receiving BCI training in a group of patients in which cortical lesions were involved [97]. A recent longitudinal observational study showed that the interhemispheric inhibition (IHI) was not associated with motor impairment after stroke and, in particular, the IHI was normal in the acute/ subacute stage and gradually became abnormal at the chronic stage [98]. Moreover, another meta-analysis summarized the way in which there is no clear evidence for the hyper-excitability of the unaffected hemisphere or imbalanced interhemispheric inhibition [92].…”
Section: Neural Mechanismmentioning
confidence: 99%
“…However, Young et al argued that this result could not be generalized to patients with cortical lesions because they found an ipsilesional lateralization during movements of affected hands at baseline toward a bilaterally distributed activity after receiving BCI training in a group of patients in which cortical lesions were involved [97]. A recent longitudinal observational study showed that the interhemispheric inhibition (IHI) was not associated with motor impairment after stroke and, in particular, the IHI was normal in the acute/ subacute stage and gradually became abnormal at the chronic stage [98]. Moreover, another meta-analysis summarized the way in which there is no clear evidence for the hyper-excitability of the unaffected hemisphere or imbalanced interhemispheric inhibition [92].…”
Section: Neural Mechanismmentioning
confidence: 99%
“…52 However, this interaction could vary depending on the time after stroke, lesion location, and measurement conditions. 26,53,54 In fact, a supportive role of the contralesional hemisphere has been suggested, at least in the subacute stage. 27,55 In the current study, the contralesional IntrahC-PSIs (δ and θ) were significantly higher in patients than in controls.…”
Section: Relationship Between Motor Recovery and The Contralesional Imentioning
confidence: 99%
“…Here, particularly contralesional primary motor cortex (M1) has been suggested to exert abnormally high inhibitory influences upon ipsilesional M1, thereby hindering motor performance and recovery [14e16]. However, recent results have suggested that these changes might also constitute a representation of the underlying recovery processes rather than a cause of poor motor recovery, given that abnormal interhemispheric inhibition emerges over time parallel to motor recovery [17]. Inconsistent results concerning the functional role of the contralesional hemisphere have been attributed to differences between subacute and chronic stroke, differences of mild, moderate, and severe motor impairment, lesion size and location, or the functional integrity of corticomotor pathways [1,9,10,18].…”
Section: Introductionmentioning
confidence: 99%